EGF coating of titanium surfaces modulates cytokines in oral mucosal primary cells exposed to TNF-α - Pansani, Taisa Nogueira [UNESP] (2023)
Objective: This study assessed the metabolism of oral mucosal cells cultured on titanium discs (Ti) coated (or not) with epidermal growth factor (EGF) and exposed to tumor necrosis factor alpha (TNF-α). Methods: Fibroblasts or keratinocytes were seeded on Ti coated or not with EGF, and then exposed to 100 ng/mL of TNF-α for 24 h. Groups were established: G1: Ti (control); G2: Ti + TNF-α; G3: Ti + EGF; and G4: Ti + EGF + TNF-α. Both cell lines were evaluated for: viability (AlamarBlue®, n = 8); interleukin 6 and 8 (IL-6, IL-8) gene expression (qPCR, n = 5), and protein synthesis (ELISA, n = 6). For keratinocytes cells, the matrix metalloproteinase type 3 (MMP-3) was evaluated by qPCR (n = 5) and ELISA (n = 6). A 3-D culture of fibroblasts was analyzed by confocal microscopy. The data were subjected to ANOVA analysis, α = 5%. Results: Increased cell viability was observed in all groups compared with G1. Enhanced gene expression and synthesis of IL-6 and IL-8 by fibroblasts and keratinocytes in G2 and modulation of hIL-6 gene expression in G4 was noted. Modulation of IL-8 synthesis occurred in keratinocytes in G3 and G4. Keratinocytes in G2 showed enhanced gene expression of hMMP-3. A 3-D culture showed more cells in G3. Fibroblasts in G2 exhibited disrupted cytoplasmic membrane. Cells in G4 showed elongated morphology with intact cytoplasm. Conclusions: EGF coating increases cell viability and modulates the response of oral cells exposed to an inflammatory stimulus.